Handbook on data envelopment analysis - Cooper, William W. (William Wager), 1914-2012; Seiford, Lawrence M.; Zhu, Joe, 1968- (International series in operations research & management science ;, 2011)
"This handbook covers DEA topics that are extensively used and solidly based. The purpose of the handbook is to (1) describe and elucidate the state of the field and (2), where appropriate, extend the frontier of DEA research. It defines the state-of-the-art of DEA methodology and its uses. This handbook is intended to represent a milestone in the progression of DEA. Written by experts, who are generally major contributors to the topics to be covered, it includes a comprehensive review and discussion of basic DEA models, which, in the present issue extensions to the basic DEA methods, and a collection of DEA applications in the areas of banking, engineering, health care, and services. The handbook's chapters are organized into two categories: (i) basic DEA models, concepts, and their extensions, and (ii) DEA applications. First edition contributors have returned to update their work. The second edition includes updated versions of selected first edition chapters. New chapters have been added on: eifferent approaches with no need for a priori choices of weights (called "multipliers) that reflect meaningful trade-offs; construction of static and dynamic DEA technologies; slacks-based model and its extensions; DEA models for DMUs that have internal structures network DEA that can be used for measuring supply chain operations; selection of DEA applications in the service sector with a focus on building a conceptual framework, research design and interpreting results"--Publisher's description.